2022
DOI: 10.5194/esd-2022-12
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrasting projection of the ENSO-driven CO<sub>2</sub> flux variability in the Equatorial Pacific under high warming scenario

Abstract: Abstract. The El Niño Southern Oscillation (ENSO) widely modulates the global carbon cycle, in particular, by altering the net uptake of carbon in the tropical ocean. Indeed, over the tropics less carbon is released by oceans during El Niño while it is the opposite for La Niña. Here, the skill of Earth System Models (ESM) from the latest Coupled Model Intercomparison Project (CMIP6) to simulate the observed tropical Pacific CO2 flux variability in response to ENSO is assessed. The temporal amplitude and spatia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, an alkalinity bias alone does not explain all the models that underestimate pCO 2,nonT , relative to pCO 2,T , as we analyze here. For example, Vaittinada Ayar et al (2022) shows that IPSL-CM6A-LR doesn't have a strong alkalinity bias, however, we find that its pCO 2,nonT : pCO 2,T variance ratio is weaker than the ratio in MRI-ESM2-0 (Figure 7b), which is a model they show with a strong alkalinity bias.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…However, an alkalinity bias alone does not explain all the models that underestimate pCO 2,nonT , relative to pCO 2,T , as we analyze here. For example, Vaittinada Ayar et al (2022) shows that IPSL-CM6A-LR doesn't have a strong alkalinity bias, however, we find that its pCO 2,nonT : pCO 2,T variance ratio is weaker than the ratio in MRI-ESM2-0 (Figure 7b), which is a model they show with a strong alkalinity bias.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies of historical simulations from the earlier CMIP5 found that FCO 2 IAV were also underestimated in models (Dong et al, 2016(Dong et al, , 2017. Results from another CMIP6 study also find that most models simulate weak FCO 2 anomalies while overestimating SST IAV (Vaittinada Ayar et al, 2022).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations